The micellization and dissociation transitions of thermo-, pH- and sugar-sensitive block copolymer investigated by laser light scattering - Y. C. Tang; J. H. Wu; J. X. Duan (eXPRESS Polymer Letters)
A triple-stimuli responsive polymer, poly(3-acrylamidophenylboronic acid)-b-poly(N-isopropylacrylamide) (PAAPBA-b-PNIPAM), has been synthesized by reversible addition-fragmentation chain transfer polymerization. Temperature, pH, and fructose induced micellization and dissociation transition of block copolymer was investigated by a combination of static and dynamic laser light scattering. PAAPBA-b-PNIPAM copolymer self-assembles into micelles with PAAPBA block as core and PNIPAM as shell in lower pH aqueous solution at room temperature. Increasing the temperature causes the micelle to shrink due to the dehydration of PNIPAM segments at pH 6.2. After the elevation of solution pH from 6.2 to 10.0, the increase in the hydrophilicity of PAAPBA block leads to an expulsion of unimers from micelles. In addition, the fructose addition further enhances the dissociation of micelles. Our experiments demonstrate that the micelle to unimer transition process proceeds via the step-by-step sequential expulsion of individual chains.